A proteomic approach to understand the impact of nodulation on salinity stress response in alfalfa (Medicago sativa L.). (6th December 2021) - Wang, Y.; Yang, P.; Zhou, Y.; Hu, T.; Zhang, P.; Wu, Y.
ABSTRACT: Symbiotic nitrogen fixation in legumes is an important source of nitrogen supply in sustainable agriculture. Salinity is a key abiotic stress that negatively affects host plant growth, rhizobium–legume symbiosis and nitrogen fixation. This work investigates how the symbiotic relationship impacts plant response to salinity stress. We assayed the physiological changes and the proteome profile of alfalfa plants with active nodules (NA), inactive nodules (NI) or without nodules (NN) when plants were subjected to salinity stress. Our data suggest that NA plants respond to salinity stress through some unique signalling regulations. NA plants showed upregulation of proteins related to cell wall remodelling and reactive oxygen species scavenging, and downregulation of proteins involved in protein synthesis and degradation. The data also show that NA plants, together with NI plants, upregulated proteins involved in photosynthesis, carbon fixation and respiration, anion transport and plant defence against pathogens. The study suggests that the symbiotic relationship gave the host plant a better capacity to adjust key processes, probably to more efficiently use energy and resources, deal with oxidative stress, and maintain ion homeostasis and health during salinity stress. Abstract : Nodulation improved salt tolerance in alfalfa.